Parental involvement in developmental disabilities across cultures - Gianluca Esposito (2022)
Background: Parents play a critical role in the early intervention/early childhood special education (EI/ECSE) services provided to young children (birth-6 years) with developmental disabilities. Aim: The aim of this systematic review was to explore parental involvement in developmental disabilities across three cultures: Mainland China, Taiwan, and Turkey. Method: According to PRISMA guidelines, we searched for articles indexed in EBSCOhost, PsycINFO, and PubMed published within the last decade for one culture (i.e., Mainland China, Taiwan, and Turkey), using the following keywords: family/parent involvement/engagement, developmental disability/disabilities, young child/children, EI/ECSE, and culture. Results: Twenty-four empirical studies were identified as relevant to our research. A majority of articles reported maternal involvement in EI/ECSE, and only a few studies included parents as intervention agents. Conclusions: This review highlights the need for future research to investigate effects of culture on parental involvement and develop culturally responsive methodical approaches to underpin meaningful parental involvement in EI/ECSE.